Buckling of thermalized elastic sheets. (April 2021) - Morshedifard, Ali; Ruiz-García, Miguel; Abdolhosseini Qomi, Mohammad Javad; Košmrlj, Andrej
Abstract: Steady progress in the miniaturization of structures and devices has reached a scale where thermal fluctuations become relevant and it is thus important to understand how such fluctuations affect their mechanical stability. Here, we investigate the buckling of thermalized square sheets under either compression or shear. We demonstrate that thermal fluctuations increase the critical buckling load compared to the classical Euler buckling load due to the enhanced scale-dependent bending rigidity for sheets that are much larger than a characteristic thermal length scale. The presented results are universal and apply to a wide range of microscopic sheets. These results are especially relevant for atomically thin 2D materials, where thermal fluctuations can significantly increase the critical buckling load because the thermal length scale is on the order of nanometers at room temperature.